Referral experiences of healthcare consumers: results from a cross-sectional study in urban slums in southeast Nigeria - Obi, Chinelo; Arize, Ifeyinwa; Nwokolo, Chukwudi; Okechi, Benard; Ebenso, Bassey; Onwujekwe, Obinna (Frontiers in Public Health, 2025)
IntroductionThe inadequate referral system in Nigeria is partly due to the proliferation of informal healthcare providers (IHPs) and constraints within formal providers in urban slums. With limited data on patient referral experiences across these providers, this paper explores referral experiences in urban slums in southeast Nigeria.MethodsThis study involved 1,025 people in eight slums in Enugu and Anambra states, using multi-stage purposive sampling. Data on referral experiences were collected through a pre-tested questionnaire and analyzed using descriptive statistics and logistic regression. Ethical approval was obtained, and informed consent was secured.ResultsIt found that only 7.4% of patients received referrals from their primary healthcare sources, mostly from patent medicine vendors, private clinics, and primary healthcare (PHC) centres to private clinics and laboratories. Verbal referrals were the dominant modality, although the types of referrals varied significantly between facilities that initiated referrals and between states.ConclusionThis paper highlights the need for innovative solutions to integrate informal healthcare providers into the formal system, improving referrals and enhancing health services in urban slums.